Kantowski–Sachs Tsallis holographic dark energy model with sign-changeable interaction - Y. Sobhanbabu (SpringerOpen, 2021)
Abstract In this work devoted to the investigation of the Tsallis holographic dark energy (IR cut-off is Hubble radius) in homogeneous and anisotropic Kantowski–Sachs Universe within the frame-work of Saez–Ballester scalar tensor theory of gravitation. We have constructed non-interacting and interacting Tsallis holographic dark energy models by solving the field equations using the relationship between the metric potentials. This relation leads to a viable deceleration parameter model which exhibits a transition of the Universe from deceleration to acceleration. In interacting case, we focus on sign-changeable interaction between Tsallis holographic dark energy and dark matter. The dynamical parameters like equation of state parameter, energy densities of Tsallis holographic dark energy and dark matter, deceleration parameter, and statefinder parameters of the models are explained through graphical representation. And also, we discussed the stability analysis of the our models.